Patient-Induced Reaction Forces and Moments Are Influenced by Variations in Spinal Manipulative Technique. Issue 2 (15th January 2017) - D'Angelo, Kevin; Triano, John J.; Kawchuk, Gregory N.; Howarth, Samuel J.
Abstract : Study Design: An in vivo biomechanical study. Objective: The aim of the present study was to quantify and compare the reaction loads for two spinal manipulation therapy (SMT) procedures commonly used for low back pain using a biomechanical computer model. Summary of Background Data: Contemporary computer-driven rigid linked-segment models (LSMs) have made it feasible to analyze low back kinetics and kinematics during various activities including SMT procedures. Currently, a comprehensive biomechanical model analyzing actual differences in loading effects between different SMT procedures is lacking. Methods: Twenty-four healthy/asymptomatic participants received a total of six SMT applications, representing all combinations of two similar SMT procedures within three patient hip flexion angles. All contact forces, patient torso kinematics, and inertial properties were entered into a dynamic three-dimensional LSM to calculate lumbar reaction forces and moments. Peak net applied force along with the maximums, minimums, and ranges for each component of the three-dimensional reaction force and moment vectors during each SMT procedure was analyzed. Results: One specific SMT technique (lumbar spinous pull) produced greater maximum anterior-posterior reaction force and both lateral bending and axial twisting reaction moments compared to the other technique (lumbar push procedure [all P  ⩽ 0.034]). SMT trials without hip flexion had lower maximum medial-lateral reaction force and range compared to those with 45 and 90 degrees of hip flexion (all P  ⩽ 0.041). There were no interactions between procedure and hip angle for any of the dependent measurements. Conclusion: The technique used to apply SMT and the participant's initial hip orientation induced significantly different actions on the low back. These findings and future research can improve patient outcomes and safety by informing clinicians on how to best use SMT given specific types of low back pain. Level of Evidence: 2